Ecological assessment of ecosystem services provided by the soil on coffee farms in Belén de Umbría, Colombia - Bedoya-Gómez, Bis Davidson (2021)
[Introduction]: The benefits provided by the soil through regulatory ecosystem services are important for the development of coffee production systems, as well as strategic for adaptation to climate change. [Objective]: This paper sought to ecologically assess the soil’s ecosystem services on coffee farms in La Cuchilla de San Juan. [Methodology]: Information was collected on the physical, chemical, and biological properties of the soil of 15 farms in two time periods. Three units of analysis referred to as windows were established, and six ecosystem services were determined (availability of nutrients, water, and microbiological activity, rooting capacity, resistance to erosion, and carbon dioxide sink). The variables with greater weight in the variability of ecosystem services were defined, and a standardization process was implemented for the adequate management of information. Three indices were generated (optimal, behavioral, and management). [Results]: It was identified that the availability of nutrients and microbiological activity is low, resistance to erosion and carbon dioxide sink varies between low and medium, while the availability of water and rooting capacity varies between medium and high. The El Consuelo property obtained the best assessment, while La Mirla, Los Pinos, and El Progreso were the properties with the lowest assessment. [Conclusions]: It was verified that anthropic dynamics have directly impacted soil conditions, and therefore, land planning is important.